On Michael Oakeshott: Scepticism and rationalism in politics. Issue 3 (December 2015) - Gamble, Andrew
Abstract : Although he is often included in the Pantheon of Conservative thinkers, Oakeshott has much to teach the modern left, saysAndrew Gamble . He examines Oakeshott's politics of scepticism, whereby sustainable and well‐adapted state institutions arise from experimentation and contingency rather than any grand political project.